Experimental study on hydrogen-rich syngas production via gasification of pine cone particles and wood pellets in a fixed bed downdraft gasifier - Aydin, Ebubekir Siddik; Yucel, Ozgun; Sadikoglu, Hasan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The main objective of this research is to investigate gasification of pine cones particles and wood pellets in a pilot scale 10 kWth downdraft fixed bed gasifier using air as an oxidizing agent. In this work, it was found that syngas produced by gasification of pinecones particles is rich in environmentally friendly hydrogen and that would be a clean alternative energy carrier for the production of clean energy. In addition, the effect of gasification temperature and equivalence ratio on the composition of syngas and gasification performance for pine cones and wood pellet were analysed comparatively. During the experimental works gasification took place with air, in a temperature range of 701-1046 degrees C, for various air equivalence ratios (0.14-0.37) and under atmospheric pressure. It is found that H-2 and CO production increased by increasing reactor temperature. Another finding is that the mean cold gas efficiency was 65% for pinecone particles and 80% for wood pellet gasification. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Pine cone gasification; Biomass; Syngas; Cold gas efficiency; BIOMASS GASIFICATION; STEAM GASIFICATION; EQUIVALENCE RATIO; COMBUSTION; CATALYSTS; ENERGY; WASTE; HUSK; PERFORMANCE; GENERATION; Chemistry; Electrochemistry; Energy & Fuels